Total Quality Management Practices in Higher Education Curriculum Development Process in Southern Africa: A Conceptual Study on the Need and Issues to Implement - Maguya Susan; Zuva Joseph; Mugijima Samuel (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
Total Quality Management (TQM) practices offer higher education institutions a transformative approach to enhance their processes, ensuring not just quality education but also organisational excellence that meets global standards. It is against this background that this book chapter ties significant issues and debates on the influence of TQM practices such as student-centric approach, continuous improvement, quality assurance systems, stakeholder involvement, performance metrics, etc., on higher education curriculum development process in Southern Africa. The chapter explores the conceptualisation of TQM practices in the context of Southern Africa’s higher education curriculum development process (curriculum design, implementation, monitoring and evaluation). The theoretical lens comprising Stakeholders, TQM and Systems theories is used to explore the indicators of quality in higher education curriculum development, TQM practices within higher education curriculum development and the nexus between TQM practices and curriculum development in higher education. Challenges such as resistance to change, resource constraints, lack of expertise, and cultural barriers were faced in creating a nexus between TQM practices and the curriculum development process in Southern Africa’s higher education is articulated. So, this chapter adds voice to the existing argument on the need for higher education institutions in Southern Africa to infuse TQM practices into the curriculum development process to enhance the curriculum design, implementation, monitoring, evaluation and review. Thus, TQM practices empower institutions to remain competitive in a rapidly evolving global landscape, addressing challenges proactively while nurturing innovation and excellence.